Plant defences mediate interactions between herbivory and the direct foliar uptake of atmospheric reactive nitrogen - Stuart A. Campbell (Nature Portfolio, 2018)
Reactive nitrogen oxides can be assimilated by leaves, though the trophic and nitrogen cycling impacts of this are unclear. Here Campbell and Vallano show foliar uptake of NO2 increases defensive metabolites, reduces herbivore consumption and growth, and herbivory reduces foliar NO2 uptake.